Water-soluble and high-temperature-resistant carbon nanotube resistance stabilizer as well as preparation method and application thereof
By using water-soluble, high-temperature resistance stabilizer, the problem of unstable resistance when the carbon nanotube film is cocured with the resin prepreg at high temperature is solved, and the high temperature resistance and resistance stability of the material are achieved.
Patent Information
- Application Number
- CN202411789168.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
When the carbon nanotube film is cocured with the resin prepreg at high temperature, displacement is prone to occur between the carbon nanotubes, resulting in unstable resistance.
A water-soluble, high temperature-resistant carbon nanotube resistance stabilizer is used, which consists of a copolymer and a tertiary amine. The copolymer is composed of acrylic acid, methacrylic acid, acrylonitrile, methacrylonitrile and acrylamide. The polymerization is initiated by an initiator to form a poly(meth)acryimide with high water resistance and high temperature deformation resistance.
The resistance stabilizer maintains the stability of the resistance at high temperature, improves the high temperature resistance of the carbon nanotube film, and matches the co-curing conditions of the high-temperature curing resin, and the cured material has high resistance to high-temperature deformation and mechanical strength.
Smart Images

Figure BDA0005174889940000051 
Figure BDA0005174889940000061 
Figure BDA0005174889940000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of structural and functional integrated composite materials, and specifically relates to a water-soluble carbon nanotube resistance stabilizer, a preparation method and an application thereof. Background Art
[0002] Carbon nanomaterials such as carbon nanotubes have good electrical conductivity, a density far lower than that of metals and a relatively high specific strength. In addition, carbon nanotubes have a high aspect ratio of up to 100-10000. When used as a conductive modifier, they also have a low percolation threshold and can achieve higher conductivity at a lower addition amount. Therefore, they have received great attention from academia and industry.
[0003] At present, carbon nanotubes have been widely used in conductive films, conductive polymers, battery electrodes and other materials. However, when carbon nanotubes are distributed in the material, their conductivity will be significantly affected by the spacing between carbon nanotubes and the filler. Conductive adhesives must be used to effectively reduce the spacing between carbon nanotubes from being affected by factors such as the flow and swelling of external liquids, thereby maintaining the stability of resistance. Existing conductive adhesives generally use materials such as polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylamide, and polyvinyl pyrrolidone. However, polyvinylidene fluoride is an oil-soluble polymer that can cause environmental pollution, while sodium carboxymethyl cellulose, polyvinyl pyrrolidone, etc. have a lower heat deformation temperature, and the resistance stability is more difficult to control when compounded with resin at high temperature. Therefore, it is urgent to develop a water-soluble, high-temperature resistant carbon nanotube resistor stabilizer. Summary of the invention
[0004] The main technical problem solved by the present invention is that when the carbon nanotube film is co-cured with the resin prepreg at high temperature, displacement between the carbon nanotubes is easy to occur, resulting in unstable and uncontrolled resistance. To this end, the present invention provides a new water-soluble, high-temperature resistant carbon nanotube resistance stabilizer and a preparation method thereof, which is mainly a conductive binder for carbon nanotubes in the co-cured carbon nanotube film, ensuring that the carbon nanotube film has good resistance to thermal deformation when compounded with a high-viscosity resin at a higher molding temperature, thereby maintaining the resistance stability of the carbon nanotube film.
[0005] At the same time, the present invention also provides an application of a carbon nanotube resistance stabilizer.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] A water-soluble, high temperature resistant carbon nanotube resistance stabilizer, the preparation raw materials include copolymer and tertiary amine;
[0008] The copolymer is formed by copolymerization of monomer A, monomer B and monomer C;
[0009] The monomer A is selected from one or both of acrylic acid and methacrylic acid;
[0010] The monomer B is selected from one or two of acrylonitrile and methacrylonitrile;
[0011] The monomer C is selected from one or two of acrylamide and methacrylamide;
[0012] In terms of molar amount, monomer A:monomer B:monomer C=40-60:40-60:0-4;
[0013] In terms of molar amount, monomer A: tertiary amine = 1: 0.2-2.
[0014] As a preferred embodiment of the present invention, based on molar amount, monomer A:monomer B:monomer C=50-60:40-50:0-3.
[0015] As a preferred embodiment of the present invention, the tertiary amine is selected from one or more of pyridine, triethylamine, triethanolamine, dimethylethanolamine, dimethylisopropanolamine, diethanolmonoisopropanolamine and the like.
[0016] Specifically, when the tertiary amine is selected from one or both of pyridine and triethylamine, the ratio of monomer A to tertiary amine is 1:0.6-1.2 in terms of molar amount.
[0017] Specifically, when the tertiary amine is selected from one or more of triethanolamine, dimethylethanolamine, dimethylisopropanolamine, and diethanolmonoisopropanolamine, the ratio of monomer A to tertiary amine is 1:0.2-1.2 in terms of molar amount.
[0018] A method for preparing a water-soluble, high temperature resistant carbon nanotube resistance stabilizer comprises the following steps:
[0019] The copolymer powder is mixed with a tertiary amine in water to obtain a carbon nanotube resistance stabilizer.
[0020] As a preferred embodiment of the present invention, the method for preparing the copolymer is: polymerizing monomer A, monomer B, and monomer C under the action of an initiator to obtain the copolymer.
[0021] Specifically, the initiator is selected from one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ADVN), dibenzoyl peroxide (BPO), and the like.
[0022] Specifically, the polymerization reaction temperature is 40-60° C. and the time is 40-100 hours.
[0023] The application of a water-soluble, high temperature resistant carbon nanotube resistance stabilizer includes but is not limited to any of the following:
[0024] (1) Used as a treating agent for (modifying) carbon nanotube films or coatings;
[0025] (2) Used as a co-dispersing modifier for carbon nanotube slurry.
[0026] As a preferred embodiment of the present invention, when the carbon nanotube resistance stabilizer is used as a treating agent for (modifying) a carbon nanotube film or a carbon nanotube coating, the application includes:
[0027] The carbon nanotube resistance stabilizer is mixed with water or diluted with water to form an aqueous treatment solution;
[0028] The (modified) carbon nanotube film or carbon nanotube coating is immersed in an aqueous treatment solution, taken out and dried, and then subjected to thermal imidization treatment (ie, a cyclization reaction and / or a dehydration reaction occurs) to obtain a carbon nanomaterial with stable resistance.
[0029] Specifically, the mass percentage concentration of the carbon nanotube resistance stabilizer in the aqueous treatment solution is 1%-16%.
[0030] Specifically, the temperature of the thermal imidization treatment is 160-240° C., and the time is 1-6 hours.
[0031] As a preferred embodiment of the present invention, when the carbon nanotube resistance stabilizer is used as a co-dispersing modifier of the carbon nanotube slurry, the application includes:
[0032] preparing an aqueous carbon nanotube slurry by mixing carbon nanotubes (with water);
[0033] A carbon nanotube resistance stabilizer or an aqueous treatment solution containing the carbon nanotube resistance stabilizer is added to an aqueous carbon nanotube slurry to prepare a co-dispersion liquid, and the carbon nanotube coating formed by the co-dispersion liquid is subjected to thermal imidization treatment (i.e., a cyclization reaction and / or a dehydration reaction occurs) to obtain a resistance-stabilized carbon nanomaterial.
[0034] Specifically, the amount of the carbon nanotube resistance stabilizer in the co-dispersion liquid is 30%-280% of the mass of the carbon nanotubes.
[0035] Specifically, the temperature of the thermal imidization treatment is 160-240° C., and the time is 1-6 hours.
[0036] As a preferred embodiment of the present invention, the application further comprises: co-curing the carbon nanomaterial with stable resistance and the high temperature curing resin prepreg in a molding process to obtain a resin composite material.
[0037] Specifically, the high temperature curing resin prepreg is selected from one or more of epoxy resin prepreg, bismaleimide resin prepreg and the like.
[0038] Beneficial effects of the present invention:
[0039] The carbon nanotube resistor stabilizer provided by the present invention has good water solubility and is environmentally friendly. The use of the resistor stabilizer to pretreat carbon nanomaterials can improve the high temperature resistance of the material and make it match the co-curing conditions of high temperature curing resin prepregs. In addition, the stabilizer after curing is insoluble in resin and water, has a high resistance to high temperature deformation, and can maintain the stability of resistance. At the same time, the carbon nanotube film or coating after curing and bonding has a high mechanical strength and good interface bonding with the resin matrix. Therefore, the carbon nanotube resistor stabilizer provided by the present invention is particularly suitable for preparing a conductive film layer co-cured with a resin material. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is described in detail below through specific embodiments. The following embodiments are intended to further illustrate the content of the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.
[0041] In the following examples and comparative examples, unless otherwise specified, the raw materials, reagents, equipment, etc. used are all commercially available products.
[0042] Solution Description
[0043] The present invention provides a water-soluble, high-temperature resistant carbon nanotube resistor stabilizer and its preparation method and application. The resistor stabilizer is high-temperature resistant and has good water solubility. After curing, it is insoluble in resin and water and has high resistance to high-temperature deformation. In addition, the carbon nanotube film or coating bonded with the resistor stabilizer has high mechanical strength and good interface bonding with the resin matrix, and is particularly suitable for conductive films co-cured with composite materials.
[0044] The current state of the art and the significant advantages of the present invention compared to the prior art:
[0045] (1) In the prior art, ionic polymers such as PVDF soluble in NMP and sodium carboxymethyl cellulose soluble in water are often used as conductive binders. The former is prone to environmental pollution and is expensive, while the latter has poor water resistance. The carbon nanotube resistance stabilizer (i.e., conductive binder) prepared by the present invention is an ionic polymer with good water solubility. It has good mixing stability when mixed with water-dispersed carbon nanotube slurry, can be converted into non-ionic polymethylimide at high temperature, has good water resistance, and has a significant conductive bonding effect compared with the prior art.
[0046] (2) In the prior art, water-soluble binders such as sodium carboxymethyl cellulose, polyacrylamide, polyacrylic acid salt, polyvinyl alcohol, etc. have low temperature resistance, are easy to decompose at high temperatures, and are easy to deform by heat, making it difficult to match the hot pressing process of high-temperature resistant composite materials at 150°C and above. However, the heat deformation temperature of poly (meth) acrylimide converted by the resistance stabilizer of the present invention reaches 200°C and above, which can match the co-curing process of high-temperature epoxy resin prepreg system and bismaleimide resin prepreg system.
[0047] (3) In addition, the water-soluble resistor stabilizer prepared by the present invention has a relatively excessive amount of carboxyl groups, and can form a good interface bonding with the resin composite material after curing.
[0048] In order to achieve the purpose of the invention, the present invention creatively makes the following design and technical improvements:
[0049] (1) In order to make the water-soluble resistor stabilizer meet the requirements of water solubility before bonding and high water resistance after bonding, the present invention is different from the existing carbon nanotube adhesive material. The resistor stabilizer with special composition and structure is innovatively designed, that is, the quaternary ammonium salt of a copolymer of acrylic acid or methacrylic acid, acrylonitrile or methacrylonitrile is used as a precursor (as shown in the following formula I, wherein the copolymer is obtained by copolymerization of methacrylic acid, methacrylonitrile and acrylamide initiated by an initiator, and the tertiary amine is triethylamine) to achieve water solubility, and poly (meth) acrylimide is used as the final body to achieve high water resistance, thereby different from the existing conductive adhesive system and achieving the unity of environmental protection and high water resistance.
[0050]
[0051] (2) In order to achieve high heat resistance of the material, especially to meet the co-curing requirements of matching high temperature resistant epoxy resin and bismaleimide resin (curing temperatures are 180°C and 200°C respectively), the monomers and their molar numbers need to be controlled as follows: 40-60 parts of acrylic acid (AA) or methacrylic acid (MAA), 40-60 parts of acrylonitrile (AN) or methacrylonitrile (MAN), 0-4 parts of acrylamide (AM) or methacrylamide (MAM). When the range is exceeded, the glass transition temperature of the thermal imidization product of the copolymer is lower than 200°C, and the resistance volatility during the molding process of the resin material becomes significantly larger, as shown in Table 1 below. The table shows the resistance change rate of the typical carbon nanotube conductive film before and after co-curing with the quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316 prepreg. The surface resistance of the carbon nanotube film used is 500Ω / sq, and the curing temperature of the resin prepreg is 180°C. When the T of the resistance stabilizer is g When the temperature is lower than the curing temperature, the resistance change rate of the carbon nanotube film increases significantly and is difficult to control.
[0052] Table 1 Resistance change rate of carbon nanotube film co-cured with QW120 / 1316 before and after curing
[0053]
[0054] (3) In order to achieve water solubility of the material, when the tertiary amine is selected as pyridine, triethylamine, triethanolamine, dimethylethanolamine, dimethylisopropanolamine, or diethanolmonoisopropanolamine, its dosage needs to be controlled to 0.2-1.2 of the molar number of acrylic acid or methacrylic acid unit. Its solubility is shown in Table 2 below.
[0055] Table 2 Solubility of copolymer quaternary ammonium salt in water
[0056]
[0057] (4) The experiment found that the carbon nanomaterial has better resistance stability after being treated with a homogeneous solution (i.e., an aqueous treatment solution containing a resistance stabilizer). The present invention particularly optimizes the raw materials and their dosage. When the solution is an emulsion, the resistance change rate is more likely to fluctuate, which is difficult to control, and the stability between batches is poor. Based on the solubility test structure in Table 2, when the tertiary amine is pyridine or triethylamine, the preferred dosage is 0.6-1.2 of the molar number of acrylic acid or methacrylic acid units; when the tertiary amine is triethanolamine, dimethylethanolamine, dimethylisopropanolamine, or diethanolmonoisopropanolamine, the preferred dosage is 0.4-1.2 of the molar number of acrylic acid or methacrylic acid units.
[0058] (5) In response to the co-curing requirements of matching high temperature resistant epoxy resin or bismaleimide resin prepreg, the present invention studies the influence of copolymer monomer composition on the interlaminar shear strength of co-cured composite materials, as shown in Table 3. Also taking QW120 / 1316 as the research system, the monomer composition of the copolymer further optimized by the experimental results is (in molar fractions): 50-60 parts of acrylic acid or methacrylic acid, 40-50 parts of acrylonitrile or methacrylonitrile, and 0-3 parts of acrylamide or methacrylamide, so that the treated carbon nanotube film or coating has better interface bonding with the resin composite material.
[0059] Table 3 Resistance change rate of carbon nanotube film co-cured with QW120 / 1316 before and after curing
[0060]
[0061] (6) Application of resistance stabilizers
[0062] 6a) The water-based carbon nanotube resistance stabilizer provided by the present invention is generally dissolved in water, and then the carbon nanotube film is treated with the water-soluble resistance stabilizer, but the mass percentage concentration of the resistance stabilizer in the water-based treatment liquid needs to be controlled to be 1%-16%. When the concentration is lower than 1%, the resistance of the carbon nanotube film and the resin prepreg after co-curing will suddenly change, and the resistance change rate will significantly increase from nearly 85%-95% to 140%-200%. When the concentration is higher than 16%, the resistance after treatment will significantly increase, especially for the carbon nanotube film with a larger resistance, the resistance after treatment will increase by even more than 100%. Therefore, it is necessary to control the mass percentage concentration of the resistance stabilizer in the water-based treatment liquid.
[0063] 6b) The aqueous carbon nanotube resistance stabilizer provided by the present invention can also be dissolved in aqueous carbon nanotube slurry and used together with carbon nanotubes, but the amount of the resistance stabilizer should be 30%-280% of the mass of the carbon nanotubes. When it is less than 30%, the resistance stability deteriorates, and the resistance change rate of the carbon nanotube film and the resin prepreg after co-curing increases to 150%-300%. When the amount is higher than 280%, the resistance of the carbon nanotubes will increase significantly, and the amount of carbon nanotube slurry used to prepare the carbon nanotube film with the same resistance will increase by more than 3 times. Therefore, when the resistance stabilizer is co-dissolved with the carbon nanotube slurry and used, its content relative to the carbon nanotubes needs to be controlled.
[0064] Example 1
[0065] This embodiment provides a water-soluble, high temperature resistant carbon nanotube resistance stabilizer, the preparation raw materials include copolymers and tertiary amines;
[0066] The copolymer is formed by copolymerization of monomer A, monomer B and monomer C;
[0067] The monomer A is methacrylic acid;
[0068] The monomer B is methacrylonitrile;
[0069] The monomer C is acrylamide;
[0070] The tertiary amine is triethylamine;
[0071] In terms of molar amount, monomer A:monomer B:monomer C=40:40:2;
[0072] In terms of molar amount, monomer A: tertiary amine = 1:1.
[0073] This embodiment provides a preparation method and application of a water-soluble, high temperature resistant carbon nanotube resistance stabilizer, comprising the following steps:
[0074] (1-1) 86.1 g (1 mol) of methacrylic acid, 67.1 g (1 mol) of methacrylonitrile, 0.05 mol of acrylamide, and 0.78 g of initiator azobisisobutyronitrile (AIBN) were mixed and stirred to dissolve evenly. The mixture was then placed in a flask, sealed, and placed in a 40°C water bath for reaction for 72 h to obtain a nearly colorless, transparent solid copolymer.
[0075] (1-2) The copolymer obtained in (1-1) is taken out, crushed into powder, and sieved with a 50-mesh screen to obtain a white powder; 1700 g of water and 101.2 g (1 mol) of triethylamine are taken out, mixed evenly, and then the white powder is added to the mixed liquid, stirred and dissolved, to obtain a treatment liquid of water-based carbon nanotube resistance stabilizer PAMNM100-100;
[0076] (1-3) taking a piece of buckypaper with a surface resistance R1 of 75Ω, immersing it in the above treatment solution, then taking it out, heating it to 160°C and keeping it for 5 hours to fully imidize the resistance stabilizer;
[0077] (1-4) The treated buckypaper is co-laminated with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the lamination order is [0|90] 20 The treated buckypaper is placed in the middle layer and then cured under the molding process of QW120 / 1316 with a curing pressure of 0.6MPa. After the curing is completed, it is cooled to below 60°C to obtain a composite material board. The resistance R2 of the co-cured buckypaper is detected.
[0078] At the same time, the untreated buckypaper was co-laminated with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the ply order was [0|90] 20 The untreated buckypaper is placed in the middle layer, and then cured under the molding process of QW120 / 1316, the curing pressure is 0.6MPa, and after the curing is completed, it is cooled to below 60°C to obtain a composite material board. The resistance R3 of the co-cured buckypaper is detected.
[0079] Experimental method: While testing the electrical resistance of the co-cured buckypaper, samples were processed separately to test the interlaminar shear strength of the composite material board.
[0080] Experimental results: The powder of the copolymer obtained in (1-1) above is well dissolved in the mixed solvent of water and triethylamine in (1-2) to form a homogeneous transparent solution. After the treatment, the R2 / R1 of the buckypaper is 0.96, while the R3 / R1 is 1.58, indicating that the resistance stabilizer significantly improves the resistance stability of the buckypaper. As for the interlaminar shear strength of the composite board, the treated composite board is 83MPa, and the untreated composite board is 85MPa, both slightly lower than the 91.5MPa of the conventional QW120 / 1316.
[0081] In other embodiments of the present invention, the triethylamine used in (1-2) can be replaced by pyridine, or by triethanolamine, dimethylisopropanolamine, etc., and the dosage is 1 mol, which basically does not affect the properties and performance of the material.
[0082] Example 2
[0083] This embodiment provides a water-soluble, high temperature resistant carbon nanotube resistance stabilizer and a preparation method and application thereof, comprising the following steps:
[0084] (2-1) 94.7 g (1.1 mol) of methacrylic acid, 67.1 g (1 mol) of methacrylonitrile, 2.1 g (0.03 mol) of acrylamide, and 0.82 g of initiator azobisisobutyronitrile (AIBN) were mixed and stirred to dissolve evenly. The mixture was then placed in a flask, sealed, and reacted in a 40°C water bath for 72 h to obtain a nearly colorless, transparent solid copolymer.
[0085] (2-2) The copolymer obtained in (2-1) above was taken out, crushed into powder, and sieved with a 50-mesh screen to obtain a white powder; 4000 g of water and 47.5 g (0.66 mol) of pyridine were taken out, mixed evenly, and then the white powder was added to the above mixed liquid, stirred and dissolved, to obtain a treatment liquid of water-based carbon nanotube resistance stabilizer PAMNM110-066;
[0086] (2-3) dispersing carbon nanotubes in water to form a homogeneous solution with a concentration of 1.6 wt%, and then coating the solution on aramid cloth to obtain a carbon nanotube conductive film attached to the aramid cloth, with a surface resistance R1 of 500 Ω, immersing the film in the above-mentioned treatment solution, and then taking it out, heating it to 180° C. and maintaining it for 3 h to fully imidize the resistance stabilizer;
[0087] (2-4) The carbon nanotube conductive film attached to the aramid cloth is co-layered with the quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the layering order is [0|90] 20The carbon nanotube conductive film is placed in the middle layer, and then cured under the molding process of QW120 / 1316, the curing pressure is 0.6MPa, and after the curing is completed, it is cooled to below 60°C to obtain a composite material board. The resistance R2 of the co-cured carbon nanotube film is detected.
[0088] At the same time, the untreated carbon nanotube conductive film attached to the aramid cloth was co-layered with the quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the layering order was [0|90] 20 The untreated carbon nanotube conductive film is placed in the middle layer, and then cured under the molding process of QW120 / 1316, the curing pressure is 0.6MPa, and after the curing is completed, it is cooled to below 60°C to obtain a composite material board. The resistance R3 of the co-cured carbon nanotube film is detected.
[0089] Experimental method: While testing the resistance of the co-cured carbon nanotube film, samples were processed separately to test the interlaminar shear strength of the composite material board.
[0090] Experimental results: The powder of the copolymer obtained in (2-1) above dissolves well in the mixed solvent of water and pyridine in (2-2) to form a homogeneous transparent solution. After the carbon nanotube conductive film is treated, R2 / R1 is 0.94, while R3 / R1 is 6.94, indicating that the resistance stabilizer significantly improves the resistance stability of the carbon nanotube conductive film. As for the interlaminar shear strength of the composite material board, the treated composite material board is 87MPa, and the untreated composite material board is 75MPa, indicating that the introduction of a resistance stabilizer with more carboxyl groups can also improve the adhesion between the layers.
[0091] Example 3
[0092] This embodiment provides a water-soluble, high temperature resistant carbon nanotube resistance stabilizer and a preparation method and application thereof, comprising the following steps:
[0093] (3-1) Take 99 g (1.15 mol) of methacrylic acid, 53.1 g (1 mol) of acrylonitrile, 0.01 mol of acrylamide, 0.78 g of initiator azobisisoheptanenitrile (ADVN), and 250 g of acetone, mix the above five substances, stir to dissolve evenly, then place in a flask, seal, and place in a 50°C water bath to react for 96 hours to obtain a nearly colorless and transparent viscous solution;
[0094] (3-2) Add 0.575 mol of triethanolamine to the viscous solution obtained in the above (3-1), stir to obtain a white solid precipitate, heat to remove acetone, and dry in a vacuum oven to obtain a white solid. Then, crush the white solid and pass it through a 20-mesh sieve to obtain a white powder, which is the water-based carbon nanotube resistance stabilizer PAANM115-050;
[0095] (3-3) dispersing carbon nanotubes in water to form a dispersion with a concentration of 2.0 wt%, adding the resistance stabilizer obtained in (3-2) to the dispersion under ultrasonic action to prepare four co-dispersions with concentrations of 0.6 wt%, 1.0 wt%, 2.0 wt% and 3.0 wt%, respectively; brushing the co-dispersions onto glass cloth to control the resistance to 300 Ω; then heating the coated glass cloth to 180° C. in an oven for 3 h to fully imidize the resistance stabilizer;
[0096] (3-4) The glass cloth treated with the co-dispersion liquid of different concentrations and the attached carbon nanotube film are co-layered with the quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the layering order is [0|90] 20 , the glass cloth-carbon nanotube film is placed in the middle layer, and then cured under the QW120 / 1316 molding process, the curing pressure is 0.6MPa, and after the curing is completed, it is cooled to below 60°C to obtain a composite material board.
[0097] Experimental method: The resistance R2 of the co-cured carbon nanotube film was detected, and samples were processed to test the interlaminar shear strength of the composite material board.
[0098] Experimental results: The co-dispersion obtained in (3-3) above has good stability and can be stored for a long time. After treatment, the resistance change rate of the conductive film obtained using different concentrations of resistance stabilizer and the interlaminar shear strength of the composite material board are shown in Table 4 below.
[0099] Table 4 Resistance change rate of conductive film and interlaminar shear strength of composite material plate
[0100] Resistance stabilizer concentration 0.6wt% 1.0wt% 2.0wt% 3.0wt% <![CDATA[R2 / R1]]> 1.15 1.01 0.95 0.94 Interlaminar shear strength (MPa) 81.5 82.1 84.3 85.2
[0101] In other embodiments of the present invention, the triethanolamine used in (3-2) can be replaced by dimethylisopropanolamine, diethanolmonoisopropanolamine, etc., and the dosage thereof is 0.575 mol, which basically does not affect the properties and performance of the material.
[0102] Example 4
[0103] This embodiment provides a water-soluble, high temperature resistant carbon nanotube resistance stabilizer and a preparation method and application thereof, comprising the following steps:
[0104] (4-1) 77.5 g (0.9 mol) of methacrylic acid, 58.4 g (1.1 mol) of acrylonitrile, 2.84 g (0.04 mol) of acrylamide, and 1.39 g of initiator azobisisobutyronitrile (AIBN) were mixed and stirred to dissolve evenly. The mixture was then placed in a flask, sealed, and reacted in a 40°C water bath for 96 h to obtain a nearly colorless, transparent solid copolymer.
[0105] (4-2) The copolymer obtained in (4-1) was taken out, crushed into powder, and sieved with a 50-mesh screen to obtain a white powder; 5000 g of water and 114 g (0.7 mol) of diethanol monoisopropanolamine were mixed evenly, and then the white powder was added to the mixed liquid, stirred and dissolved to obtain a treatment liquid of PANM082-070, a resistance stabilizer for water-based carbon nanotubes (mass percentage concentration of 2.64 wt%);
[0106] (4-3) A piece of buckypaper with a surface resistance R1 of 75 Ω is taken and immersed in the above treatment solution, then taken out and heated to 240°C for 1 hour to allow the resistance stabilizer to be fully imidized, and then vacuumed to remove any residual tertiary amine;
[0107] (4-4) The treated buckypaper is co-laminated with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the lamination order is [0|90] 20 The treated buckypaper is placed in the middle layer and then cured under the QW120 / 1316 molding process with a curing pressure of 0.6 MPa. After the curing is completed, it is cooled to below 60°C to obtain a composite material board.
[0108] Experimental method: The resistance R2 of the co-cured buckypaper was tested, and the samples were processed to test the interlaminar shear strength of the composite material board.
[0109] Experimental results: The powder of the copolymer obtained in (4-1) above dissolves well in the mixed solvent of water and diethanol monoisopropanolamine in (4-2) to form a homogeneous transparent solution. After the treatment, the R2 / R1 of the buckypaper is 0.97, indicating that the resistance stabilizer significantly improves the resistance curing stability of the buckypaper. As for the interlaminar shear strength of the composite board, the treated composite board is 79.5MPa.
[0110] In other embodiments of the present invention, the diethanol monoisopropanolamine used in (4-2) can be replaced by triethanolamine, dimethyl isopropanolamine, etc., and the dosage thereof is 0.7 mol, which basically does not affect the properties and performance of the material.
[0111] Example 5
[0112] This embodiment provides a water-soluble, high temperature resistant carbon nanotube resistance stabilizer and a preparation method and application thereof, comprising the following steps:
[0113] (5-1) Take 103.3 g (1.2 mol) of methacrylic acid, 59 g (0.88 mol) of methacrylonitrile, 4.26 g (0.06 mol) of acrylamide, 0.42 g of initiator azobisisoheptanenitrile (ADVN) and 0.42 g of dibenzoyl peroxide (BPO) (total 0.84 g), and 250 g of acetone, mix the above five substances, stir to dissolve evenly, then place in a flask, seal, and place in a 50°C water bath to react for 96 hours to obtain a nearly colorless and transparent viscous solution;
[0114] (5-2) 80.2 g (0.9 mol) of dimethylethanolamine was added to the viscous solution obtained in the above (5-1), and the mixture was stirred to obtain a white solid precipitate. The acetone was removed by filtering and heating, and the mixture was dried in a vacuum oven to obtain a white solid. The white solid was then crushed and passed through a 20-mesh sieve to obtain a white powder, which is the water-based carbon nanotube resistance stabilizer PAANM136-075.
[0115] (5-3) dispersing carbon nanotubes in water to form a dispersion with a concentration of 1.5 wt %, adding the above-mentioned resistor stabilizer to the dispersion under ultrasonic action to prepare two co-dispersions with concentrations of 1.5 wt % and 3.0 wt %, respectively; brushing the above-mentioned co-dispersions onto glass cloth to control the resistance to 300 Ω; then heating the coated glass cloth to 200° C. in an oven for 3 h to fully imidize the resistor stabilizer;
[0116] (5-4) The glass cloth treated with different concentrations of the co-dispersed liquid and the attached carbon nanotube film are co-layered with the quartz fiber fabric reinforced bismaleimide resin prepreg QW280 / 5429, and the layering order is [0|90] 20 The glass cloth-carbon nanotube film is placed in the middle layer and then cured under the molding process of QW280 / 5429. The curing pressure is 0.6MPa and the curing temperature is 200℃. After the curing is completed, it is cooled to below 60℃ to obtain a composite material board.
[0117] Experimental method: The resistance R2 of the co-cured carbon nanotube film was detected, and samples were processed to test the interlaminar shear strength of the composite material board.
[0118] Experimental results: The R2 / R1 of the composite material plate obtained above for the two co-dispersed liquids were 1.15 and 1.01 respectively, while the resistance change rate of the carbon nanotube film without adding resistance stabilizer was 2.81, indicating that the resistance stabilizer significantly improved the curing resistance stability of the carbon nanotube film. As for the interlaminar shear strength of the composite material plate, the composite material plates corresponding to the two co-dispersed liquids were 85.4MPa and 89.2MPa respectively, while the composite material plate without adding resistance stabilizer was 85.1MPa.
[0119] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A water-soluble, high temperature resistant carbon nanotube resistance stabilizer, characterized in that: The raw materials for preparing the carbon nanotube resistance stabilizer include copolymers and tertiary amines; The copolymer is formed by copolymerization of monomer A, monomer B and monomer C; The monomer A is selected from one or both of acrylic acid and methacrylic acid; The monomer B is selected from one or two of acrylonitrile and methacrylonitrile; The monomer C is selected from one or two of acrylamide and methacrylamide; In terms of molar amount, monomer A:monomer B:monomer C=40-60:40-60:0-4; In terms of molar amount, monomer A: tertiary amine = 1: 0.2-2.
2. The carbon nanotube resistance stabilizer according to claim 1, characterized in that: In terms of molar amount, monomer A:monomer B:monomer C=50-60:40-50:0-3.
3. The carbon nanotube resistance stabilizer according to claim 1, characterized in that: The tertiary amine is selected from one or more of pyridine, triethylamine, triethanolamine, dimethylethanolamine, dimethylisopropanolamine, and diethanolmonoisopropanolamine.
4. A method for preparing a water-soluble, high temperature resistant carbon nanotube resistance stabilizer as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The copolymer powder is mixed with a tertiary amine in water to obtain a carbon nanotube resistance stabilizer.
5. The preparation method according to claim 4, characterized in that: The preparation method of the copolymer is: polymerizing monomer A, monomer B and monomer C under the action of an initiator to obtain the copolymer.
6. The preparation method according to claim 5, characterized in that: The initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dibenzoyl peroxide; And / or, the polymerization reaction temperature is 40-60° C. and the time is 40-100 hours.
7. An application of a water-soluble, high temperature resistant carbon nanotube resistance stabilizer as claimed in any one of claims 1 to 3, characterized in that: When the carbon nanotube resistance stabilizer is used as a treating agent for (modifying) a carbon nanotube film or a carbon nanotube coating, the application includes: Forming the carbon nanotube resistance stabilizer into an aqueous treatment solution; The (modified) carbon nanotube film or carbon nanotube coating is immersed in an aqueous treatment solution, taken out and dried, and then subjected to thermal imidization treatment to obtain a carbon nanomaterial with stable resistance; The mass percentage concentration of the carbon nanotube resistance stabilizer in the aqueous treatment liquid is 1%-16%; The temperature of the thermal imidization treatment is 160-240° C. and the time is 1-6 hours.
8. An application of a water-soluble, high temperature resistant carbon nanotube resistance stabilizer as claimed in any one of claims 1 to 3, characterized in that: When the carbon nanotube resistance stabilizer is used as a co-dispersion modifier for carbon nanotube slurry, the application includes: preparing the carbon nanotubes into an aqueous carbon nanotube slurry; adding a carbon nanotube resistance stabilizer or an aqueous treatment solution containing the carbon nanotube resistance stabilizer to an aqueous carbon nanotube slurry to prepare a co-dispersion solution, and subjecting the carbon nanotube coating formed by the co-dispersion solution to a thermal imidization treatment to obtain a resistance-stabilized carbon nanomaterial; The amount of the carbon nanotube resistance stabilizer in the co-dispersion liquid is 30%-280% of the mass of the carbon nanotubes; The temperature of the thermal imidization treatment is 160-240° C. and the time is 1-6 hours.
9. The use according to claim 8, characterized in that: The application also includes: co-curing the resistance-stable carbon nanomaterial and the high-temperature curing resin prepreg in a molding process to obtain a resin composite material.
10. The use according to claim 9, characterized in that: The high temperature curing resin prepreg is selected from one or both of epoxy resin prepreg and bismaleimide resin prepreg.
Citation Information
Patent Citations
Water-soluble adhesive for lithium ion battery, preparation method for water-soluble adhesive, electrode sheet and battery
CN111139002A
Preparation method of polymethacrylimide hybrid aerogel
CN112521653A
Water-based adhesive, preparation method thereof and application of water-based adhesive in negative electrode of lithium battery
CN116200147A